Basic concepts of linear algebra - Isaak, S.; Manougian, M.N. (New York : Norton & Company, 1976)
The purpose of this text is to introduce students of mathematics, the sciences, and engineering to the basic concepts of linear algebera.
Chapter 0. Preliminaries -- Chapter 1. Matrix algebra -- Chapter 2. Vector spaces -- Chapter 3. Linear independence and finite dimensional vector spaces -- Chapter 4. Determinants -- Chapter 5. Dot products and orthogonality -- Chapter 6. Linear transformations and matrices -- Chapter 7. Eigenvalues and eigenvectors -- Chapter 8. Some applications.
Includes index.
Keywords: ALGEBRA -- LINEAR